HEALTH IS INDEED A MAN'S THING: A REFLECTIVE ANALYSIS OF PROSTATE CANCER - Araújo, Simone Rodrigues da Silva; de Gois, Eliana Teles; da Silva, Kelly Viviane; Silva, Francisca Juliana de Assunção; Rodrigues, Judite Santos; Lopes, Mayane Santana de Oliveira; Siqueira, Reinaldo Santos; de Magalhães, Jardel Robert Henning Rodrigues; de Farias, Maria Lúcia; Medeiros, Elaine Rocha; Costa e Silva, Carolina; Borba, Sanderli Dionísio Pereira (Seven Editora, 2025)
Prostate cancer is a malignant disease resulting from the disordered growth of cells, with morphological, structural and metabolic alterations, as well as accelerated division and genetic mutations. This neoplasm can invade adjacent organs and, in more severe cases, can reach places far from its origin. It is a disease that is usually associated with several triggering factors, a situation that proves its epidemiological importance in the country. It is a comprehensive review of the literature based on the narrative synthesis of scientific evidence. In clinical practice, it is observed that, in most cases, men only seek care when the disease is already installed, with greater chances of complications and early deaths. Because of this, it is of fundamental importance to include the male population in the health-disease process, so that the strong social and cultural influence rooted over the years and generations can give way to protagonism in health.DOI: https://doi.org/10.56238/sevened2024.037-154